Fungal fruitbodies and soil macrofauna as indicators of land use practices on soil biodiversity in Montado - Azul, Anabela Marisa; Mendes, Sara Margarida; Sousa, José Paulo; Freitas, Helena (Agroforestry Systems, 2011)
The impacts of land use on soil biodiversity are still poorly understood, although soil fungi and macrofauna are recognized to provide beneÞts to ecosystems. Here, we tested whether land use practices used to control shrub density inßuences the fruiting macromycetes (ectomycorrhizal-forming fungiÑ ECMFÑand saprobes) and soil macrofauna diversity and abundance in Montado ecosystems. To address this inßuence, we conducted a 2-yearsÕ period monitoring of fungi fruitbodies and macrofauna in sixteen experimental plots in Montado landscape in southern Portugal. A total of 4,881 frutibodies (57 taxa of ECMF and 64 taxa of saprobic fungi) and 3,667 soil invertebrates (73 species and morphospecies) were monitored in the experimental plots. There was greater losses in sporocarps production and taxa composition, particularly the ECMF, in plots where shrub density was controlled by permanent grazing (Ca) or involving cutting practices followed by soil tillage (M), in comparison with cutting practices with no soil tillage (Cu) and the control (C). The ECMFLaccaria laccata and Xerocomus subtomentosus exhibited a close relation with C and Cu plots while the saprobes, e.g., Entoloma conferendum, were associated to Ca and M plots. Most species associated to Cu plots were present in C plots during the 2 years, but not in Cu after the cutting practices (in the second year of sampling). Regarding soil macrofauna, higher values of taxa and species richness were observed in C and Cu plots in the Þrst year of sampling. The ant species Aphaenogaster senilis and several Staphylinid morphospecies exhibited a close relation with M plots, whilst most spider families were directly associated to C and Cu plots. After the shrub cutting practices, higher values of taxa and species richness of soil macrofauna were observed in M and Ca plots; the presence of species with a high competitive ability to colonize disturbed areas faster might explain the results. Contrary to the frutibodies production and diversity, species richness and abundance within soil macrofauna were identical between Cu and C in 2004. Thus, fruiting macromycetes and soil macrofauna diversity and abundance in MontadoÕs, appear highly sensitive to land use and somewhat reßected a trend of severity to the current shrub management practices.
Keywords: Ecosystems monitoring; Fungal fruit-body; fungal fruit-body á soil; land use; macrofauna á; montado; Quercus suber L.; soil macrofauna